2022
DOI: 10.3390/antiox12010041
|View full text |Cite
|
Sign up to set email alerts
|

Antiproliferative and Proapoptotic Effects of Erucin, a Diet-Derived H2S Donor, on Human Melanoma Cells

Abstract: Melanoma is the most dangerous form of skin cancer and is characterized by chemotherapy resistance and recurrence despite the new promising therapeutic approaches. In the last years, erucin (ERU), the major isothiocyanate present in Eruca sativa, commonly known as rocket salads, has demonstrated great efficacy as an anticancer agent in different in vitro and in vivo models. More recently, the chemopreventive effects of ERU have been associated with its property of being a H2S donor in human pancreatic adenocar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 68 publications
0
2
0
Order By: Relevance
“…E-Cadherin (E-CAD) and N-Cadherin (N-CAD) expression levels were evaluated in iSP-treated A375 (1 µg/mL for 48 h) via extracellular staining with APC-Cy7 antihuman CD324 (E-CAD) (67A4, Biolegend, 1:50) and FITC antihuman CD325 (N-CAD) (8C11, Biolegend, 1:50) as previously reported [56].…”
Section: Flow Cytometry Analysismentioning
confidence: 99%
“…E-Cadherin (E-CAD) and N-Cadherin (N-CAD) expression levels were evaluated in iSP-treated A375 (1 µg/mL for 48 h) via extracellular staining with APC-Cy7 antihuman CD324 (E-CAD) (67A4, Biolegend, 1:50) and FITC antihuman CD325 (N-CAD) (8C11, Biolegend, 1:50) as previously reported [56].…”
Section: Flow Cytometry Analysismentioning
confidence: 99%
“…Among them, erucin (4-methylthiobutyl isothiocyanate) is one of the major components of leaves obtained from the enzymatic hydrolysis of glucoerucin. As demonstrated in a large number of in vitro and in vivo studies, erucin exerts protective effects against several types of human cancers, including breast cancer [ 8 , 11 , 12 , 13 , 14 , 15 ]. Remarkably, recent findings revealed that the protective effect of erucin relies on its intrinsic capacity to slowly release hydrogen sulfide (H 2 S), which is one of three gasotransmitters, along with nitric oxide (NO) and carbon monoxide (CO), which act in our body to modulate numerous biological processes [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…H 2 S-releasing compounds have also emerged as potential therapeutics for various types of cancers. Ianaro, Ercolano, and co-workers examine the effects of erucin (ERU), a compound derived from the dietary source, on human melanoma cell lines [ 4 ]. ERU was found to exert a significant inhibitory effect on human melanoma cell lines.…”
mentioning
confidence: 99%